Electrocatalytic Microelectrode Detectors for Choline and Acetylcholine following Separation by Capillary Electrophoresis - Mukherjee, Jhindan (2009)
Two electrocatalytic enzyme modified microelectrode systems were employed as end-column amperometric detectors of choline (Ch) and acetylcholine (ACh) following separation by capillary electrophoresis (CE). Horseradish peroxidase crosslinked in an Os based redox polymer hydrogel (HRP-Os) was physically adsorbed on Au microelectrodes followed by chemical crosslinking of the enzymes acetylcholinesterase (AChE) and choline oxidase (ChO). An alternative approach utilized the deposition of the transition metal catalyst, Prussian Blue (PB), on Pt microelectrodes as the electrocatalyst. Utilizing butyrylcholine (BuCh) as an internal standard, the HRP-Os/AChE-ChO and PB/AChE-ChO electrodes exhibited excellent linear responses from 2–2000 μM and 10–2000 μM, respectively, for both Ch and ACh. Detection limits of 0.1 μM or 38 amol were determined for the HRP-Os/AChE-ChO electrode. The limit of detection for ACh and Ch at the PB/AChE-ChO electrode was 5 μM or 9.5 fmol. The electrodes were operated at potentials of +0.10 and −0.10 V vs. Ag/AgCl (3M NaCl), respectively, and thus minimized the potential response from oxidizable interferences. In addition, both electrocatalytic electrodes showed good operational stability for more than 70 hours. The enhanced detection capability of the HRP-Os/AChE-ChO and PB/AChE-ChO electrodes in combination with efficient CE separation of Ch and ACh provides a new sensitive and selective strategy for monitoring and quantifying these cholinergic biomarkers in biological fluids.